Review: The Oxford Handbook of Dance and the Popular Screen, edited by Melissa Blanco Borelli - Blades, Hetty (The International Journal of Screendance, 2015)
Dance on screen is by no means a new phenomenon, however the analytic consideration of popular dance on screen is a relatively new addition to dance studies. The Oxford Handbook of Dance and the Popular Screen, edited by Melissa Blanco Borelli, takes Sherril Dodds' seminal work Dance on Screen from 2001 as a point of departure, in order to "establish a body of contemporary readings about dance in a popular screen context."